Star kids 5 (Revised Edition) : A Series of theme-based English text books for the students of Elementary School - Herina Nirmala; Aquilina Nikke Paramita; Christina Maryeni; Margareta Ratnaningdyah; Maria Tintun; Flora Maharani (Kanisius, 2019)
Buku ini merupakan buku Bahasa Inggris dasar untuk kelas enam SD